Antibody information used for Western blot. - Yingying Chen (500738) (2025)
Purpose Chronic atrophic gastritis (CAG) is a prevalent condition that can undergo precancerous lesions of gastric cancer (PLGC) and thus progression to gastric cancer. Weifuchun (WFC), a traditional Chinese herbal compound, is employed in CAG treatment and microbial homeostasis modulation. We aimed to explore the role of WFC in CAG from the perspective of gastrointestinal microbiota. Methods PLGC rats were developed by N-methyl-N’-nitro-N-nitrosoguanidine treatment. Then, various doses of WFC were administered to the rats and WFC compositions were analyzed. The pathological changes and inflammatory markers of the rats were assessed. Key proteins in the interleukin (IL)-6/Janus Kinase 1/Signal Transducer and Activator of Transcription 3 (JAK1/STAT3) pathway were evaluated, alongside fecal microbial analysis through 16S ribosomal DNA sequencing. Results Most compounds identified from WFC were nucleosides, flavones, organic acids, phenylpropanoids and other components. WFC treatment alleviated intestinal metaplasia and dysplasia caused by atrophic gastritis in PLGC rats. WFC also reduced inflammatory marker levels, and inhibited the IL-6/JAK1/STAT3 pathway for PLGC rats. The higher the dose of WFC was administrated, the better the effects on the aforementioned results. Simultaneously, WFC improved the CAG gastrointestinal microbiota homeostasis. Interestingly, WFC increased Coprocuccus abundance, which was significantly correlated with proliferating cell nuclear antigen and IL-6 levels. Conclusions WFC alleviated PLGC by regulating the balance of gastrointestinal microbiota and influencing the IL-6/JAK1/STAT3 pathway, revealing the potential connection between gastrointestinal microbiota and CAG progression. This study is the first to link gastrointestinal microbiota homeostasis and IL-6/JAK1/STAT3 pathway, providing novel insights into WFC’s multi-targeted therapeutic mechanism on CAG.